Do overeducated individuals have increased risks of ill health?: a Swedish population‐based cohort study. Issue 6 (28th March 2016) - Hultin, Hanna; Lundberg, Michael; Lundin, Andreas; Magnusson, Cecilia
Abstract: Previous studies indicate that the increasing educational level in many post‐industrial nations may imply that subgroups of the population work in occupations for which they are overeducated. We aimed to investigate whether overeducation is associated with future self‐rated health and psychological distress. The analytical sample consisted of 21, 159 participants from the Stockholm Public Health Cohort. Individuals with upper secondary or university education, who in 2006 or 2007 had occupations requiring less education, were considered overeducated. The outcomes were self‐rated health (SRH) and psychological distress in 2010. Overeducated women had an increased risk of less than good SRH, compared to university‐educated women in matching occupations (adjusted odds ratios (OR): 2.44 confidence intervals (CI): 1.32–4.51 for overeducated women with secondary school education), but not compared to less educated women in the same occupational class (adjusted OR: 0.87 CI:0.32–2.38 for overeducated women with secondary school education). We found no increased risk of less than good SRH for overeducated men, and no association between overeducation and psychological distress for either sex. The results indicate that overeducation is not per se associated with onset of less than good SRH or psychological distress in a short‐term perspective, and the findings support education expansion as a means of improving public health.